Penerapan Metode Saw Untuk Sistem Pendukung Keputusan Mahasiswa Berprestasi Pada Institut XYZ - Yana Mulya Hayri, Dipo; Resad Setyadi (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2024)
Student achievement is one of the important factors in the success of students in the future. Student achievement in higher education is generally measured by the Grade Point Average (GPA). Decision Support System has concept "The system is a collection of interrelated elements that are responsible for processing input (input) so as to produce output (output)” . The Simple Additive Weighting (SAW) method is known as the weighted addition method. The basic concept in the SAW method is to find the weighted sum of the performance ratings on each alternative in all attributes. In the method of collecting data through this questionnaire, the authors obtained data in the form of IPS, GPA, Achievements, Attendance, and SKS. This data collection was carried out at institute XYZ, in the Information Systems study program, with a total of 42 students. The research method is basically a scientific way to obtain information with a specific purpose and use. The research method is the method used by researchers in collecting research data